Histories of Law, or the Laws of History: Can Jane Eyre Cross the Wide Sargasso Sea? - Jukić-Gregurić, Tatjana (Array, 1998)
Jean Rhys's novel Wide Sargasso Sea (1966), conceived as a "prequel" to Charlotte Bronte's Jane Eyre (1874), is one of the earliest British explorations into the field of historiographic matafiction. Especially interesting in this sense is its treatment of the historical and fictioanl divides separating the 1966 discourse from its Victorian predecessor, but also its subversion of the feminist and colonial premises of Jane Eyre. Since both stories rely heavily on Rhy's and Bronte's accounts of marriage, the aim of my paper was an analysis of the institution of marriage in its function of a potent discursive nexus sanctioning, as it were, cultural histories of both texts.